Adolescent confidentiality: Understanding and practices of health care providers. Issue 2 (1st February 2014) - Wadman, Ruth; Thul, Deborah; Elliott, April S; Kennedy, Andrea Pritchard; Mitchell, Ian; Pinzon, Jorge L
Abstract: BACKGROUND: Adolescent confidentiality may present practice challenges for health care providers related to family, medical, ethical, legal, social and bureaucratic processes. It is unclear how health care providers understand and practice confidentiality with adolescents in Canada. OBJECTIVE: To investigate the knowledge and practice of health care providers at Alberta Children's Hospital (Calgary, Alberta), and to inform practice about the adolescent's right to confidentiality. METHODS: The present study was a voluntary, anonymous online survey. Invitations to participate were sent through the paediatric facility's electronic mailing list to all currently employed health care providers who potentially engaged in caregiving interactions with adolescents. The survey consisted of 15 closed items and seven open comment items. Closed items were analyzed using descriptive statistics and open comments were analyzed using manifest thematic coding. RESULTS: A total of 389 responses were received, representing health care providers in many disciplines. A variety of practices related to adolescent confidentiality and widespread misunderstanding of this issue were apparent. Respondents' comments revealed individual and team knowledge gaps regarding adolescent and parent/guardian rights, and the difference between the constructs of consent to treatment and the provision of confidential health care for adolescents. CONCLUSIONS: While health care providers regard confidentiality as paramount, the present survey revealed a wide variation in understanding and practices regarding confidential care for adolescents. This was revealed in both the qualitative and quantitative data. The authors' recommended strategies to improve the understanding and practice of adolescent confidentiality include: encouraging individuals' examination of beliefs; postsecondary instruction; knowledge-translation strategies within programs; and institution-directed guidelines and policy.